Lipid‐Labeling Facilitates a Novel Magnetic Isolation Procedure to Characterize Pathogen‐Containing Phagosomes. (28th December 2012) - Steinhäuser, Christine; Heigl, Ulrike; Tchikov, Vladimir; Schwarz, Jeanette; Gutsmann, Thomas; Seeger, Katrin; Brandenburg, Julius; Fritsch, Jürgen; Schroeder, Josef; Wiesmüller, Karl‐Heinz; Rosenkrands, Ida; Walther, Paul; et al.
<x xml:space="preserve">Abstract</x> Here we describe a novel approach for the isolation and biochemical characterization of pathogen‐containing compartments from primary cells: We developed a lipid‐based procedure to magnetically label the surface of bacteria and visualized the label by scanning and transmission electron microscopy (SEM, TEM). We performed infection experiments with magnetically labeled Mycobacterium avium, M. tuberculosis and Listeria monocytogenes and isolated magnetic bacteria‐containing phagosomes using a strong magnetic field in a novel free‐flow system. Magnetic labeling of M. tuberculosis did not affect the virulence characteristics of the bacteria during infection experiments addressing host cell activation, phagosome maturation delay and replication in macrophages in vitro. Biochemical analyses of the magnetic phagosome‐containing fractions provided evidence of an enhanced presence of bacterial antigens and a differential distribution of proteins involved in the endocytic pathway over time as well as cytokine‐dependent changes in the phagosomal protein composition. The newly developed method represents a useful approach to characterize and compare pathogen‐containing compartments, in order to identify microbial and host cell targets for novel anti‐infective strategies.